Development of Android-Based Marbles Chem Hydrocarbon Mobile Game Media to Improve Motivation and Learning Outcomes of 11th Grade Science Students - Muhidah, Izzatul; Agustini, Rudiana (Universitas Pendidikan Mandalika, 2023)
One of the uses of ICT in the world of education can be in the form of game media because students are actively involved in learning so that it can increase motivation. Learning outcomes are related to motivation, if the motivation given is more appropriate, the more successful the learning will be. This study aims to obtain feasible Marbles Chem Hydrocarbon media to increase student motivation and learning outcomes based on three aspects, namely validity, practicality, and effectiveness. The research method used is research and development / Research and Development (R&D) adaptation from Plomp (2013), consisting of three phases, namely the Preliminer Phase, the Prototype Making Phase, and the Evaluation Phase. Limited trials were conducted in 11th Grade Science (MIPA) of State Senior High School (SMAN) 20 Surabaya. Validity is obtained from three validators. Practicality is obtained from the results of response questionnaires, observation of student activities, and the implementation of learning. effectiveness is obtained from ARCS motivation questionnaire sheets and student learning outcomes. Media validity on content validity and construct validity barada in the range of scores 4 and 5 with valid and very valid criteria. Practicality is reviewed based on observations of learning implementation, student response questionnaires, and observations of student activities with an average percentage of 98.47%, 96.98%, and the results of observations of relevant activities are greater than irrelevant activities, namely 205.16 > 6.43. The effectiveness of the media obtained pretest-posttest increased from 60 incomplete categories to 87.69 complete categories and the ARCS motivational questionnaire increased from 55.32 with the moderately effective category to 95.85 very effective categories. Based on the results of validity, practicality and effectiveness, Marbles Chem Hydrocarbon media is suitable to be used as a learning medium on Hydrocarbon material.